Safety and immunogenicity of rAd26 and rAd5 vector-based heterologous prime-boost COVID-19 vaccine against SARS-CoV-2 in healthy adolescents: an open-label, non-randomized, multicenter, phase 1/2, dose-escalation study - Tukhvatulin, Amir I.; Dolzhikova, Inna V.; Dzharullaeva, Alina S.; Grousova, Daria M.; Kovyrshina, Anna V.; Zubkova, Olga V.; Zorkov, Ilya D.; Iliukhina, Anna A.; Shelkov, Artem Y.; Erokhova, Alina S.; Popova, Olga; Ozharovskaia, Tatiana A.; et al. (Frontiers in Immunology, 2023)
To protect young individuals against SARS-CoV-2 infection, we conducted an open-label, prospective, non-randomised dose-escalation Phase 1/2 clinical trial to evaluate the immunogenicity and safety of the prime-boost "Sputnik V" vaccine administered at 1/10 and 1/5 doses to adolescents aged 12-17 years. The study began with the vaccination of the older cohort (15-to-17-year-old participants) with the lower (1/10) dose of vaccine and then expanded to the whole group (12-to-17year-old participants). Next, 1/5 dose was used according to the same scheme. Both doses were well tolerated by all age groups. No serious or severe adverse events were detected. Most of the solicited adverse reactions were mild. No significant differences in total frequencies of adverse events were registered between low and high doses in age-pooled groups (69.6% versus 66.7%). In contrast, the 1/5 dose induced significantly higher humoral and T cell-mediated immune responses than the 1/10 dose. The 1/5 vaccine dose elicited higher antigen-binding (both S and RBD-specific) as well as virusneutralising antibody titres at the maximum of response (day 42), also resulting in a statistically significant difference at a distanced timepoint (day 180) compared to the 1/10 vaccine dose. Higher dose resulted in increased cross-neutralization of Delta and Omicron variants.